Working in Social Cooperatives. The Case of Greater Poland Region of Poland - Baranowski, Mariusz (Studia Historiae Oeconomicae, 2012)
The present paper concentrates on the issue of work in the context of operation of social cooperatives, defined by the law as social enterprises (Act of 27 April 2006). In order to illustrate the character of operation of this new form of economic life organisation / form of entrepreneurship, which, apart from purely market-oriented purposes (generating profits), also has social objectives (social and professional re-integration of persons excluded or threatened with exclusion), I will use the data collected in the course of the project called “Social Exclusion: Diagnosis and Mechanisms of Counteraction in Greater Poland Region”.